2006
DOI: 10.1111/j.1365-2222.2006.02595.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of interleukin‐25 (IL‐17E)‐induced pulmonary inflammation and airways hyper‐reactivity

Abstract: IL-25 potently (single dose) induces sustained AHR and acute pulmonary inflammation with eosinophilia. IL-25-induced AHR is dependent on the production of Th type-2 cytokines, and removal of IL-13 and its signal transduction pathway prevents IL-25-induced airways inflammation and AHR. IL-25 potently induces inflammatory cascades that may exacerbate allergic airways inflammation by promoting Th type-2 cytokine responses in conjunction with the up-regulation of factors (eotaxin and arg-I) that can amplify inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 27 publications
5
83
1
Order By: Relevance
“…Transgenic expression of IL-25 in the bronchial epithelium results in mucus production and recruitment of macrophages and eosinophils to the airways (39). Similarly, intranasal instillation of recombinant IL-25 promotes AHR, eosinophilic inflammation, mucus hypersecretion, and production of Th2-type cytokines in the lung (41). In contrast, blockade of IL-25 reduces airway inflammation and Th2 cytokine production in an acute allergen-induced asthma model (39,42).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Transgenic expression of IL-25 in the bronchial epithelium results in mucus production and recruitment of macrophages and eosinophils to the airways (39). Similarly, intranasal instillation of recombinant IL-25 promotes AHR, eosinophilic inflammation, mucus hypersecretion, and production of Th2-type cytokines in the lung (41). In contrast, blockade of IL-25 reduces airway inflammation and Th2 cytokine production in an acute allergen-induced asthma model (39,42).…”
Section: Discussionmentioning
confidence: 94%
“…Although IL-25 does not directly induce smooth muscle contraction, stimulation of cells with IL-25 increases their expression of components of the extracellular matrix, namely procollagen-a1 and lumican mRNA (44). Instillation of a single dose of IL-25 to the airways of mice has been shown to result in AHR, which is maintained for at least 16 days (41). Conversely, blocking IL-25 in an acute experimental model of allergic asthma has been demonstrated to prevent AHR (42).…”
Section: Discussionmentioning
confidence: 99%
“…Although classic animal models of experimental asthma depend on sensitized Th2 cells, intranasal administration of IL-25 or IL-33 in mice have also been reported to induce an asthma phenotype with airway hyperresponsiveness, eosinophilic inflammation, mucus hypersecretion, and Th2 cytokine production in the lung [14,25,34]. Since ILC2s are reported to release cytokines in response to IL-25 or IL-33 stimulation [7,9], we hypothesized that pulmonary ILC2s contribute to airway inflammation in cytokineinduced asthma.…”
Section: Pulmonary Ilc2s Are Induced In Il-25-and Il-33-induced Asthmamentioning
confidence: 99%
“…150,154 IL-17E-induced mucous hypersecretion and AHR have been suggested to be primarily dependent on IL-13-STAT6 signaling. 150,155 In addition to the induction of Th2 cytokines, one study showed that prolonged IL-17 expression in the lung induced NKT cell-dependent pulmonary arterial remodelling. 156 IL-17E also contributes to VEGF signaling-induced angiogenesis via the Erk/MAPK and PI3K/Akt pathways in asthma.…”
Section: Il-17dmentioning
confidence: 99%